(untitled) (Fiep Bulletin - online, 2013)
Descriptive exploratory study conducted in a general hospital, private, large-scale. The target population consisted of 25 professional nurses working in the sector of pediatrics in the period of data collection, which was held after a favorable opinion of the ethics committee of the UFRN respecting the resolution 196/96. RESULTS: A group of 25 professional nurses, and nurses 24% and 76% technical nursing. Regarding the use of criterion to assess the pain, 88% of professionals in the study uses a criterion to assess pain in children and 12% of them do not use any discretion. Wow (64%), facial expression (28%), behavior (12%), and the combination of combined criteria: cry / facial expressions (20%), crying and behavior (8%), are the criteria used by professionals. From interventions, 60% of those surveyed is restricted to pharmacological methods for relief of pain, 20% assis the child with dressing and comfort, 12% have both pipelines and 8% did not intervene. CONCLUSION: The results also show that there is a fragility about the activities of the professionals related to the control and relief of pain indicating that most, is basically limited to pharmacological methods and not see the problem more broadly impossible better assistance.